A COMPARATIVE ANALYSIS OF CONSUMER PURCHASE INTENTION IN SELECTING ONLINE SHOP USING ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH (CASE STUDY: LAZADA, BUKALAPAK, TOKOPEDIA) - Mukuan, Phoebe R.J.S; Lambey, Linda; Rumokoy, Farlen S. (Universitas Sam Ratulangi, 2019)
Abstract: Online shopping becomes one of the ways of shopping. It is more practical, time and energy efficient. The consumers have many choices to buy the online products. Through the online shopping, the purchasers can shop a wide range of needs without having to meet in person with the seller. The purpose of this research is to determine which online shop is most preferred by consumers and what criteria that influences the most. This research used Analytical Hierarchy Process (AHP) to compare each online shop based on the criteria: Trust, Perceived Ease of Use, Perceived Usefulness, Website Attractiveness, Perceived Enjoyment and Perceived Riskiness. This research was conducted between September to October 2016 in Manado City. The respondents are 100 people who have already purchased in the three online shops. The respondents were chosen by using purposive sampling. The result shows that Trust is the most important criteria with score (0.429081), followed by Perceived Ease of Use (0.248430045), Perceived Usefulness (0.176987646), Website Attractiveness (0.095409043), Perceived Enjoyment (0.070826483) and the last is Perceived Riskiness (0.042530205). The result also shows that, Lazada is the most preferred by the respondents, followed by Bukalapak and Tokopedia.Â Keyword: consumer purchase intention, online shop, analytical hierarchy process